Matrix Metalloproteinase-8 Inhibitor Ameliorates Inflammatory Responses and Behavioral Deficits in LRRK2 G2019S Parkinson's Disease Model Mice - Kim, Taewoo; Jeon, Jeha; Park, Jin-Sun; Park, Yeongwon; Kim, Jooeui; Noh, Haneul; Kim, Hee-Sun; Seo, Hyemyung (Biomolecules & therapeutics, 2021)
Parkinson's disease (PD) is a neurodegenerative disorder that involves the loss of dopaminergic neurons in the substantia nigra (SN). Matrix metalloproteinases-8 (MMP-8), neutrophil collagenase, is a functional player in the progressive pathology of various inflammatory disorders. In this study, we administered an MMP-8 inhibitor (MMP-8i) in Leucine-rich repeat kinase 2 (LRRK2) G2019S transgenic mice, to determine the effects of MMP-8i on PD pathology. We observed a significant increase of ionized calcium- binding adapter molecule 1 (Iba1)-positive activated microglia in the striatum of LRRK2 G2019S mice compared to normal control mice, indicating enhanced neuro-inflammatory responses. The increased number of Iba1-positive activated microglia in LRRK2 G2019S PD mice was down-regulated by systemic administration of MMP-8i. Interestingly, this LRRK2 G2019S PD mice showed significantly reduced size of cell body area of tyrosine hydroxylase (TH) positive neurons in SN region and MMP-8i significantly recovered cellular atrophy shown in PD model indicating distinct neuro-protective effects of MMP-8i. Furthermore, MMP-8i administration markedly improved behavioral abnormalities of motor balancing coordination in rota-rod test in LRRK2 G2019S mice. These data suggest that MMP-8i attenuates the pathological symptoms of PD through anti-inflammatory processes.Parkinson's disease (PD) is a neurodegenerative disorder that involves the loss of dopaminergic neurons in the substantia nigra (SN). Matrix metalloproteinases-8 (MMP-8), neutrophil collagenase, is a functional player in the progressive pathology of various inflammatory disorders. In this study, we administered an MMP-8 inhibitor (MMP-8i) in Leucine-rich repeat kinase 2 (LRRK2) G2019S transgenic mice, to determine the effects of MMP-8i on PD pathology. We observed a significant increase of ionized calcium- binding adapter molecule 1 (Iba1)-positive activated microglia in the striatum of LRRK2 G2019S mice compared to normal control mice, indicating enhanced neuro-inflammatory responses. The increased number of Iba1-positive activated microglia in LRRK2 G2019S PD mice was down-regulated by systemic administration of MMP-8i. Interestingly, this LRRK2 G2019S PD mice showed significantly reduced size of cell body area of tyrosine hydroxylase (TH) positive neurons in SN region and MMP-8i significantly recovered cellular atrophy shown in PD model indicating distinct neuro-protective effects of MMP-8i. Furthermore, MMP-8i administration markedly improved behavioral abnormalities of motor balancing coordination in rota-rod test in LRRK2 G2019S mice. These data suggest that MMP-8i attenuates the pathological symptoms of PD through anti-inflammatory processes.